Factors Determining Behavioral Intentions to Use Islamic Fintech: Millennials Generation - Eva Nuurul Azhar; Sita Deliyana Firmialy (Department of Management, Faculty of Economics and Business, Brawijaya University, 2024)
Technological advances are consistently rising, with Indonesia witnessing a yearly increase in internet penetration rates. Technological advancements foster innovation in diverse industries, such as finance and banking. Financial technology is an innovative application of current technology in the financial sector, demonstrating the increasing efficiency of the financial system and services. Sharia financial technology exhibits slower growth in comparison to traditional Fintech. Nevertheless, sharia-compliant financial technology presents significant prospects. This study aims to identify the elements that influence the behavioral intentions of the millennial age in using Sharia financial technology. This study employs a quantitative research approach and utilized a questionnaire as the primary instrument for data collection. The acquired data was analyzed using the Structural Equation Model (SEM) and Smart-PLS. This study had a total of 106 participants. The research findings indicate that the acceptance model and technology utilization substantially influence the promotion of behavioral intentions to adopt Sharia Fintech. The distinguishing feature of this study is its emphasis on millennials and the factors that influence their preference to utilize Islamic financial technology.